Effect of Deposition Time on Optical and Solid State Properties of Chemically Deposited Iron Copper Sulphide (FeCuS) Ternary Thin Films - Livinus , Okoli Nonso; . Eric , Udechukwu Ifeanyi; Theresa , Okpaneje Onyinye (African Journal of Education,Science and Technology (AJEST), 2016)
Ternary Thin films of FeCuS were grown on glass substrates by Chemical Bath Deposition (CBD) technique above room temperature of 353K at a varying time of deposition. Iron (III) trioxonitrate nanohydrate, copper chloride dihydrate and thiourea were used as sources for iron, copper and sulphur ions respectively. The optical characterization was done by using a Janway UV- VIS spectrophotometer in the wavelength range of 300 nm – 1100 nm. The optical absorbance of the films was determined directly from the spectrophotometer. Other properties such as optical thickness, transmittance, reflectance, refractive index, extinction coefficient and optical band gap energy were calculated. These films showed high absorbance in UV region and low values in VIS – NIR region. The transmittance of the films is low in UV region and high in VIS – NIR regions. A band gap energy range between 2.50 eV and 2.80 eV were obtained. The reflectance is low in all regions of electromagnetic spectrum studied. Refractive index of the films ranged from 2.60 to 1.10. Enhanced Mini – Material Analyzer X – ray Diffractometer was used to determine the crystal structure and crystallite size. The grain size obtained was 326.50 nm – 432.29 nm for different time of depositions. Olympus Optical Microscopy was used to capture the photomicrographs of the films. These films could be applied in solar cells fabrication optoelectronic devices,anti-reflective coating of glasses and other numerous applications.